Fatal Pulmonary Embolism In Total HIP Replacement - Fredin, H O; Nillius, A S (Thrombosis and Haemostasis, 1981)
A retrospective study of fatal pulmonary embolism (FPE) was carried out in 1498 hips during 1968 - 1979. Dextran 70 was given as thromboprophylaxis, no anaphylactic reactions were registered. Sixteen patients died within 3 months, autopsy was made in fourteen cases. Nine patients died from FPE within 3 months, eight patients were autopsied.Comparing this group with a surviving group chosen by random from the whole material we found that acute attacks of pleuritic chest pain was more common (p < 0.001) as well as previous operations for orthopedic and gynecological reasons (p < 0.05) in the group of FPE. No difference could be found between the groups concerning blood loss, amount of transfusion, sex, operated side, type of prosthesis and body weight.Conclusions: 1. FPE was the most common cause of death within 3 months after THR.2. The incidence of FPE was 0.6% in 1498 patients treated with Dextran 70 prophylaxis.3. Acute attacks of pleuritic chest pain in the postoperative period is an important symptom which should be followed by a lungscan to rule out pulmonary embolism.4. Only chest radiogram is not sufficient for the evaluation of acute pleuritic chest pain after THR.5. Heparin therapy for a short period did not prevent FPE in cases with scintigraphic diagnosis of pulmonary embolism.